2006
DOI: 10.1002/1097-0142(19830701)52:1<140::aid-cncr2820520125>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

α1 Isoenzyme of alkaline phosphatases clinical importance and value for the detection of liver metastases

Abstract: Measurement of the α1 (fast liver) fraction of alkaline phosphatases in the serum for 217 cancer patients, 92 patients with nonmalignant hepatic affections and 131 controls, revealed that the α1 fraction offers better global value (94%), sensitivity (96%), and specificity (93%) than γGT or total alkaline phosphatase determinations for the detection of liver metastases during cancer. Initial data from study of the time of appearance of the α1 fraction reveals that this fraction shows up earlier than rises in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Furthermore, there is evidence that analysis of serumderived tumor-specific isoforms of alkaline phosphatase may increase the predictive accuracy of this marker. 35,36 Apart from CEA, no other blood-derived variable has been used in prognostic scoring in CRCLM, to our knowledge. We found that determination of serum alkaline phosphatase and albumin provides significant independent information about prognosis in all patients referred for surgery and in patients who underwent liver resection.…”
Section: Validation Of the Prognostic Scoring Systemmentioning
confidence: 99%
“…Furthermore, there is evidence that analysis of serumderived tumor-specific isoforms of alkaline phosphatase may increase the predictive accuracy of this marker. 35,36 Apart from CEA, no other blood-derived variable has been used in prognostic scoring in CRCLM, to our knowledge. We found that determination of serum alkaline phosphatase and albumin provides significant independent information about prognosis in all patients referred for surgery and in patients who underwent liver resection.…”
Section: Validation Of the Prognostic Scoring Systemmentioning
confidence: 99%
“…An increased expression of liver ALP at the surface of hepatocyte plasma membranes, accompanied by the shedding of liver plasma membrane fragments is thought to be responsible for the presence of BALP in these patients (Van Hoof and De Broe 1994;Deng et al 1996). The clinical value of the BALP isoform in detecting liver metastasis has been evaluated by several investigators (Viot et al 1981;Viot et al 1983;Karmen et al 1984;Nishio et al 1986;Yeh et al 1989;Yorio et al 2000).…”
Section: Introductionmentioning
confidence: 99%